Salt marsh restoration surprise: A subordinate species accumulates and shares nitrogen while outcompeting salt marsh dominants - Morzaria-Luna, Hem Nalini; Zedler, Joy B. (Frontiers in Ecology and Evolution, 2022)
Selectively planting native species could guide ecosystem development toward wetland restoration targets, once we understand how influential species function, alone and in combination. Knowing that Triglochin concinna (arrow grass, Juncaceae) accumulates N in its perennial roots, we asked if it could influence N dynamics on an excavated salt marsh plain at Tijuana Estuary, in southern California, by (a) accumulating N in roots and shoots, (b) reducing biomass of other marsh plain plants or (c) sharing N with neighbors as its litter decomposed and released N. In field and greenhouse experiments, Triglochin had low shoot biomass (0.96 ± 0.5 g m-2 in field plots and 17.64 ± 2.2 g m-2 in greenhouse pots), high root:shoot ratios (4.3 in the field and 2.0 in the greenhouse), and high tissue N content (1.9 ± 0.2% in the field and 1.7 ± 0.1% in the greenhouse). Two productive perennials, Sarcocornia pacifica (pickleweed) and Frankenia salina (alkali heath), outgrew Triglochin; yet these biomass dominants produced 44-45% less shoot biomass in greenhouse pots with Triglochin than without. We did not find this reduction in the field where roots were unconfined, however. In the greenhouse, δ15N values were higher for species grown with 15N-enriched Triglochin, indicating that this species made N available to its neighbors. The δ15N values for plants grown in the field were higher than background levels, also indicating that the 7species marsh plain plant assemblage took up N released by Triglochin. We conclude that Triglochin can influence the restoration of salt marsh vegetation by accumulating N and releasing its tissue N to neighbors as leaves and roots decompose, while at the same time reducing the biomass of neighbors. The seasonally deciduous Triglochin is low in shoot biomass, yet competitively superior in N uptake. Because this often-ignored species is not tidally-dispersed, we suggest restoration plantings, including tests of its ability to facilitate diversity where S. pacifica might otherwise form monocultures.